2004
DOI: 10.1002/jmv.20151
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers of clonality and identity in epstein–barr virus‐associated B‐cell lymphoproliferative disease

Abstract: Epstein-Barr virus (EBV)-associated B-cell lymphoproliferative disease may be polyclonal, oligoclonal, or monoclonal. The degree of tumor clonality reflects the disease pathogenesis and may have implications for disease diagnosis, prognosis, and treatment. In this study, specimens of EBV-associated B-cell lymphoproliferative disease obtained from immunocompromised hosts were analyzed for molecular markers of cellular and virologic clonality and virologic identity. Each tumor specimen was assessed for immunoglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…However, the clonality of the viral episome enabled the identification of clonality in carcinomas. Analyses of Ig rearrangement and EBV termini confirmed the relationship between viral and cellular clonality (Katz et al 1989;Walling et al 2004). Multiple subsequent studies have identified clonal EBV in most of malignancies associated with EBV including Hodgkin's lymphoma, salivary gland carcinoma, and gastric cancer, and clonal termini have become one of the criteria indicating a etiologic role for EBV in these cancers (Raab-Traub et al 1991;Weiss et al 1988).…”
Section: Aspects Of Ebv and Cancer Biology Discovered In Npcmentioning
confidence: 85%
See 1 more Smart Citation
“…However, the clonality of the viral episome enabled the identification of clonality in carcinomas. Analyses of Ig rearrangement and EBV termini confirmed the relationship between viral and cellular clonality (Katz et al 1989;Walling et al 2004). Multiple subsequent studies have identified clonal EBV in most of malignancies associated with EBV including Hodgkin's lymphoma, salivary gland carcinoma, and gastric cancer, and clonal termini have become one of the criteria indicating a etiologic role for EBV in these cancers (Raab-Traub et al 1991;Weiss et al 1988).…”
Section: Aspects Of Ebv and Cancer Biology Discovered In Npcmentioning
confidence: 85%
“…Thus, in the absence of recognition by cytotoxic lymphocytes, EBV-infected lymphocytes are able to switch to the transforming growth mode of expression resulting in lymphoma. In some cases, multiple clonal tumors are identified in different organs (Walling et al 2004). This detailed understanding of the EBV immune response has led to the first clearly effective viralspecific immunotherapy or prophylaxis where EBV-specific CTLs are expanded ex vivo by exposure to EBV transformed lymphocytes (Heslop et al 1999).…”
Section: Classes Of Ebv-associated Malignanciesmentioning
confidence: 97%
“…Clonality can be assessed using immunoglobulin heavy chain gene rearrangement and EBV termini assays [66]. Flow cytometric analysis can also be used to determine monoclonality of B-cell lesions and T-cell lesions when immunoglobulin light chain (j or k) restriction or loss of surface or cytoplasmic immunoglobulin and abnormal T-cell antigen expression or loss is identified, respectively [67].…”
Section: Diagnosismentioning
confidence: 99%
“…(3). EBV sequence variation is a recognized phenomenon (2-4) and has been used for EBV genotyping (4). Sequencing of the carboxyl-terminal region of the LMP1 gene showed that multiple variants (one to seven clones) may coexist in an individual (3).…”
mentioning
confidence: 99%